Automated guided vehicle dispatching based on combinatorial optimisation to minimise job waiting time on shop floors. (11th October 2019) - Huang, Shiyang; Hu, Guiping
On manufacturing shop floors, automated guided vehicles (AGVs) have been widely adopted and configured for material handling, and they are dispatched to transport jobs between work centres. In this paper, two AGV dispatching strategies based on combinatorial optimisation are proposed. AGVs are assigned to work centres according assignment optimisation models to minimise the total waiting time of jobs. In the decision horizon, status of AGVs and jobs in or between work centres are predicted. The AGV dispatching strategies take future transportation requests into consideration and optimally configure transportation resources, such that material handling can be more efficient than those adopting classic AGV assignment rules in which only the current request is considered. The strategies were demonstrated in a case study and compared with classic AGV assignment rules including random assignment and nearest vehicle/shortest travel time rule. The results showed that the proposed dispatching strategies could better control job waiting time on the shop floors compared to classic AGV assignment rules.